Implementation of Ethics in Public Services towards Good Governance in The Perspective of Public Administration - Arip Rahman Sudrajat (Journal of Social Science, 2023)
Ethics is closely related to the achievement of good governance. One of the problems that arises in the administration of government is that there are still violations committed by public organizers, so it is necessary to have moral values as guidelines, and government organizers must stick to the administration of government in order to achieve good. This study aims to find out how ethics in public service which is good governance from the perspective of public administration. In this study, the type of research used is qualitative research. Data collection techniques by searching literature, literature, scientific journals and statutory documents collected according to the research topic. Public administration provides a set of ethical principles, normative standards, codes of ethics, and moral virtues for the bureaucracy to apply to public services. If all dimensions of service are well implemented in the service delivery process, high-quality bureaucratic performance can be produced.